Development of a Low-Cost Electronic Wheelchair with Obstacle Avoidance Feature - Arboleda, Edwin Romeroso; Alegre, Mary Christine Tumambing; Idica, Kathleen Felix (Journal of Mechatronics, Electrical Power and Vehicular Technology, 2015)
A low-cost electronic wheelchair was designed and developed which can perform the similar functions and features as a commercially available wheelchair. It also provides obstacle avoidance capability as added value. The electronic wheelchair was realized by modification of a lightweight manual wheelchair. It uses two electric motors each of 320 W 24 V DC, 5-24 VDC 6 A H-bride drivers, and a 12 V 17 Ah rechargeable lead acid battery. It equipped with switches, joystick, infrared sensors and ultrasonic sensors. A GizduinoAtMega 328 microcontroller is used to read and interpret commands. User’s acceptance evaluation results shows that the developed low-cost wheelchair is able to receive and interpret commands provided by the joystick, detect if a person is seated on it, navigate to avoid obstacles as well as to detect edge and stairs. Technical evaluation result shows that on a flat surface it could move at the speed of around 39.9 m/minute without load and 32 m/minute with 80 kg load. At 10 degrees inclined surface, the maximum weight limit is 30 kg with the speed of 12 m/minute. At 20 degrees inclined surface, the maximum weight limit is 10 kg with the speed of 3 m/minute. Regarding cost, it is just a fraction of a cost compared to the commercially available model. Therefore, the developed wheelchair offers an option for potential users who cannot afford to buy the commercially available one.